In Vitro Activities of Novel trans-3,5-Disubstituted Pyrrolidinylthio-1β-Methylcarbapenems with Potent Activities against Methicillin-Resistant Staphylococcus aureus and Pseudomonas aeruginosa - Nagano, Rie (American Society for Microbiology, 2000)
The in vitro activities of the novel 1β-methylcarbapenems J-111,225, J-114,870, and J-114,871, which have a structurally unique side chain that consists of a trans-3,5-disubstituted 5-arylpyrrolidin-3-ylthio moiety at the C-2 position, were compared with those of reference antibiotics. Among isolates of both methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant coagulase-negative staphylococci (MRCoNS), 90% were inhibited by J-111,347 (prototype), J-111,225, J-114,870, and J-114,871 at concentrations of 2, 4, 4, and 4 μg/ml (MICs at which 90% of isolates are inhibited [MIC(90)s]), respectively, indicating that these agents were 32- to 64-fold more potent than imipenem, which has an MIC(90) of 128 μg/ml. Although these drugs were less active in vitro than vancomycin, which had MIC(90)s of 1 and 2 μg/ml for MRSA and MRCoNS, respectively, the new carbapenems displayed better killing kinetics than vancomycin. The potent anti-MRSA activity was ascribed to the excellent affinities of the new carbapenems for penicillin-binding protein 2a of MRSA. Since the new carbapenems also exhibited good activity against gram-positive and -negative bacteria including clinically important pathogens such as penicillin-resistant Streptococcus pneumoniae, Haemophilus influenzae, members of the family Enterobacteriaceae, Pseudomonas aeruginosa, and Clostridium difficile, as well as MRSA, the novel carbapenems are worthy of further evaluation.